The Earnings Management Strategy of Indebted Non-Listed Firms: The Case of Italy - Matonti, Gaetano; Iuliano, Giuseppe; Tucker, Jon (International Journal of Accounting and Financial Reporting, 2023)
Design/methodology/approach: For a sample of Italian non-listed firms that file full financial statements, we conduct a cross sectional regression analysis to determine whether the managers of indebted firms complement real activity-based (REM) with accrual-based (AEM) earnings management. To model each technique, we estimate OLS regressions with robust standard errors to avoid heteroscedasticity problems. Purpose: This research analyses whether the managers of highly indebted Italian non-listed firms, financed mainly by bank-loans, are likely to undertake real activity-based earnings management (REM) and accrual-based earnings management (AEM) as complementary activities to boost the impact of earnings management (EM) on reported earnings and achieve desired earnings targets. Findings: Consistent with the extant literature, we find that indebted firms are likely to complement REM with AEM to enhance their creditworthiness. We also provide evidence that high-quality audit companies constrain neither REM nor AEM initiatives. Finally, firms suffering from financial problems are less likely to engage in either initiative as they are under greater scrutiny from lenders. Originality: The paper investigates the complementary use of accrual-based and real activity-based earnings management techniques in non-listed firms, suffering from a high pressure from lenders in the case of indebtedness. Practical implications: This research should be of interest to banks, managers, and standard setters as it highlights the earnings management strategy employed by firms with a high leverage ratio and provides evidence on the relative costs associated with each earnings management technique.